Moving Beyond Energy Homeostasis: New Roles for Glucagon-like Peptide-1 in Food and Drug Reward - Reddy, India A. (2013)
Glucagon-like peptide-1 (GLP-1), a hormone and neuropeptide, is known to regulate energy homeostasis in part through an established central role in controlling food intake. Historically this central role has largely been attributed to GLP-1 receptor signaling in the brainstem and hypothalamus. However, emerging data indicate that GLP-1 also contributes to non-homeostatic regulation of food reward and motivated behaviors in brain reward centers, including the ventral tegmental area and nucleus accumbens. The hypothesis that GLP-1 signaling modulates reward circuitry has provided the impetus for studies demonstrating that GLP-1 attenuates reward for psychostimulants and alcohol. Here, we examine current evidence for GLP-1-mediated regulation of food and drug reward and use these findings to hypothesize mechanisms of action within brain reward centers.